1864. Implementation of the National Healthcare Safety Network's (NHSN) Antimicrobial Use Option in the US Veterans Affairs (VA) Medical Facilities. (26th November 2018) - Lewis, Julia; Slager, Stacey; Barraza, Jeremy; Roselle, Gary; Mayer, Jeanmarie; Jones, Makoto
Abstract: Background: Inappropriate or unnecessary use of antibiotics exacerbates antimicrobial resistance and can lead to adverse clinical outcomes. To address this issue, NHSN created the Antimicrobial Use (AU) Option to report antimicrobial use within acute care facilities. A pilot program was started to implement AU reporting in VA in 2013. Methods: With support from VA Antimicrobial Stewardship Task Force and NHSN, we deployed one team to focus on implementation and another on technical aspects. We used an iterative recruitment approach with four cohorts to date (Tiers), starting with highly engaged facilities with strong stewardship infrastructure. Our implementation approach (Figure 1) was based on the Promoting Action on Research Implementation (PARiHS) framework for successful implementation of evidence into clinical practice. We evaluated our implementation with focus groups conducted using Skype chat to collect feedback from participants about the implementation process. Group 1 contained six participants from Tiers 1 and 2. Group 2 had three participants from Tiers 3 and 4. Questions were constructed using the PARiHS framework (Table 1). An implementation team member conducted interviews, monitored the discussion, then coded major themes of responses. Results: To date, there are over 90 facilities reporting AU to NHSN. Major themes to responses are summarized in Table 1. Overall, focus group participants were supportive of the program, but there were differences between early and later adopters. Conclusion: A coordinated, centralized approach to facilitating implementation of NHSN AU reporting has been successful so far. Major themes from focus group responses did differ in some categories depending on tier in a way that appears concordant with the theory diffusion of innovation, e.g., early tiers were enthusiastic despite a lack of institutional support while later tiers reported being motivated by regulatory requirements and had solid institutional support. More research would further inform how to efficiently implement complex programs in large systems. Disclosures: All authors: No reported disclosures.